Association between endostatin and mortality in patients with acute dyspnoea, with or without congestive heart failure: a single-centre, prospective, observational study - Axel C Carlsson; Caroline Heijl; Ardavan M Khoshnood; Alexander Yaghoubi; Per Erik Wändell; Torgny Wessman (BMJ Open)
Objective The aim of this study was to assess associations between endostatin levels and short-term mortality in unsorted acute hospitalised dyspnoea patients with or without congestive heart failure (CHF), adjusted for common cardiovascular risk factors.Design, setting and participants In this prospective observational study, 723 hospitalised patients who visited the emergency department at Skåne University Hospital, Sweden, between 2013 and 2018 were included. Of these, 276 had a history of CHF. The association between endostatin levels and 1 month and 3-month mortality was evaluated, stratified by whether patients had a history of CHF or not.Results Patients with prior CHF had higher endostatin levels, higher short-term mortality and were more likely to have CHF as discharge diagnosis. In a fully adjusted model, endostatin was independently associated with 3-month mortality (HR=1.01 per 1 ng/mL increment of endostatin; 95% CI 1.00 to 1.02; p=0.016). No evidence of association was identified with 1-month mortality.Conclusions Endostatins are potential biomarkers for 3 months’ mortality in patients hospitalised with CHF seeking emergency care with acute dyspnoea. Further studies are needed in different settings to assess the predictive value of endostatins in patients with CHF.